Racial differences in longitudinal Alzheimer's disease biomarkers among cognitively normal adults. Issue 12 (25th February 2022) - Xiong, Chengjie; Luo, Jingqin; Schindler, Suzanne E.; Fagan, Anne M.; Benzinger, Tammie; Hassenstab, Jason; Balls‐Berry, Joyce E.; Agboola, Folasade; Grant, Elizabeth; Moulder, Krista L.; Morris, John C.
Abstract: Introduction: Longitudinal changes in Alzheimer's disease (AD) biomarkers, including cerebrospinal fluid (CSF) analytes, amyloid uptakes from positron emission tomography (PET), structural outcomes from magnetic resonance imaging (MRI), and cognition, have not been compared between Blacks and Whites. Methods: A total of 179 Blacks and 1180 Whites who were cognitively normal at baseline and had longitudinal data from at least one biomarker modality were analyzed for the annual rates of change. Results: CSF amyloid beta (Aβ)42/Aβ40 declined more slowly ( P  = .0390), and amyloid (PET) accumulated more slowly ( P  = .0157), in Blacks than Whites. CSF Aβ42 changed in opposite directions over time between Blacks and Whites ( P  = .0039). The annual increase in CSF total tau and phosphorylated tau181 for Blacks was about half of that for Whites. Discussion: Longitudinal racial differences in amyloid biomarkers are observed. It will be important to comprehensively and prospectively examine the effects of apolipoprotein E genotype and sociocultural factors on these differences.